Novel transforming growth factor beta receptor I kinase inhibitor galunisertib (LY2157299) in advanced hepatocellular carcinoma. (3rd June 2019) - Faivre, Sandrine; Santoro, Armando; Kelley, Robin K.; Gane, Ed; Costentin, Charlotte E.; Gueorguieva, Ivelina; Smith, Claire; Cleverly, Ann; Lahn, Michael M.; Raymond, Eric; Benhadji, Karim A.; Giannelli, Gianluigi
Abstract: Background and Aims: We assessed the activity of galunisertib, a small molecule inhibitor of the transforming growth factor beta (TGF‐β1) receptor I, in second‐line patients with hepatocellular carcinoma (HCC) in two cohorts of baseline serum alpha fetoprotein (AFP). Methods: Patients with advanced HCC who progressed on or were ineligible to receive sorafenib, Child‐Pugh A/B7 and ECOG PS ≤1 were enrolled into Part A (AFP ≥ 1.5× ULN) or Part B (AFP < 1.5× ULN). Patients were treated with 80 or 150 mg galunisertib BID for 14 days per 28‐day cycle. Endpoints were time‐to‐progression (TTP) and changes in circulating AFP and TGF‐β1 levels, as well as safety, pharmacokinetics, progression‐free survival and overall survival (OS). Results: Patients (n = 149) were enrolled with median age 65 years. Median TTP was 2.7 months (95% CI: 1.5‐2.9) in Part A (n = 109) and 4.2 months (95% CI: 1.7‐5.5) in Part B (n = 40). Median OS was 7.3 months (95% CI: 4.9‐10.5) in Part A and 16.8 months (95% CI: 10.5‐24.4) in Part B. OS was longer in AFP responders (>20% decrease from baseline, Part A) compared to non‐responders (21.5 months vs 6.8 months). OS was longer in TGF‐β1 responders (>20% decrease from baseline, all patients) compared to non‐responders. The most common Grade 3/4 treatment‐related adverse events were neutropenia (n = 4) and fatigue, anaemia, increased bilirubin, hypoalbuminemia and embolism (each, n = 2). Conclusions: Galunisertib treatment had a manageable safety profile in patients with HCC. Lower baseline AFP and a response in AFP or TGF‐β1 levels (vs no response) correlated with longer survival. Trial Registration Number: NCT01246986 at ClinicalTrials.gov. Abstract : See Editorial on Page 1391